The Global Colony: A Comparative Analysis of National Security-Based Foreign Investment Regimes in the Western Hemisphere - Colin Stapleton (Washington University Law Review, 2015)
In 1975, the United States took steps to prevent its national security from being undermined by foreign investment through the creation of the Committee for Foreign Investment in the United States (CFIUS). CFIUS is an interagency committee meant to review and approve mergers and acquisitions of US companies that have a relation, however tangential, to national security. CFIUS has evolved since its inception from a relatively benign review mechanism to a sophisticated shield with the power to block almost any questionable foreign transactions involving US companies. This Note compares CFIUS to the investment regulations of Mexico, Chile, and Brazil, specifically those regulations focused on guaranteeing the national security of these countries. Each country’s regulatory regime is compared to CFIUS to determine their relative strength and potential to be undermined by a foreign power. This comparison is buttressed by background on the Latin American economy to illustrate the importance of natural resources and their effect on the definition of “national security” within the region. This Note continues by drawing a relation between the inadequacy of these investment regimes and the prevalence of nationalization by various regional governments. It suggests that nationalization might serve to compensate for these investment regimes by enabling governments to reassert control over critical industries and resources. Finally, this Note argues that the turmoil created by the region’s ineffective investment regimes creates a security risk for the United States and the Western Hemisphere as a whole. To reduce this risk, the United States should work with its hemispheric neighbors to ensure they have robust legal regimes to protect themselves and ensure they maintain economic independence.
Keywords: Foreign Investment; Foreign investment regulations; CFIUS; National security